Evaluation of BD Onclarity™ HPV Assay on Self-Collected Vaginal and First-Void Urine Samples as Compared to Clinician-Collected Cervical Samples: A Pilot Study - Marianna Martinelli; Chiara Giubbi; Illari Sechi; Fabio Bottari; Anna Daniela Iacobone; Rosario Musumeci; Federica Perdoni; Narcisa Muresu; Andrea Piana; Robert Fruscio; Fabio Landoni; Clementina Elvezia Cocuzza (Diagnostics, 2022)
The accuracy of available HPV molecular assays on self-samples needs to be evaluated as compared to clinician-collected samples. This pilot study aimed to investigate the BD Onclarity™ HPV assay on vaginal and first-void urine samples. Sixty-four women referred to colposcopy for cervical dysplasia performed a vaginal self-collection and provided a first-void urine sample, after informed consent. A cervical specimen was collected during the clinician examination. All samples were tested using BD Onclarity™ HPV assay on the BD Viper™ LT System. Overall positive agreement (OPA) between cervical and self-sample results was evaluated using Cohen’s kappa value (κ). Using a clinical cut-off of 38.3 Ct for HPV 16 and 34.2 Ct for other HR genotypes, compared to cervical sample, the self-collected vaginal sample OPA was 85.9%, and κ = 0.699. Without a clinical cut-off, the OPA was 95.3%, and the κ = 0.890. Data obtained comparing cervical and urine samples showed an OPA of 87.5% with a κ = 0.79 using a clinical cut-off, and an OPA of 90.6% with a κ = 0.776 without a clinical cut-off. Data showed a substantial agreement between both self-collected and clinician-collected samples. A specific clinical cut-off analysis should be considered based on type of sample analysed.